Resistance of Pseudomonas to Quaternary Ammonium Compounds. I. Growth in Benzalkonium Chloride Solution - Adair, Frank W. (1969)
Resistant cells of Pseudomonas aeruginosa and a waterborne Pseudomonas sp. (strain Z-R) were able to multiply in nitrogen-free minimal salts solution containing various concentrations of commercially prepared, ammonium acetate-buffered benzalkonium chloride (CBC), a potent antimicrobial agent. As the CBC concentration increased, growth increased until a point was reached at which the extent of growth leveled off or was completely depressed. Minimal salts solutions of pure benzalkonium chloride (PBC) containing no ammonium acetate did not support bacterial growth. When ammonium acetate was added to PBC solutions in the same concentrations found in CBC solutions, growth patterns developed that were comparable to those found with CBC. Likewise, (NH(4))(2)SO(4) added to PBC solutions supported growth of both organisms. P. aeruginosa was initially resistant to CBC levels of 0.02% and it was adapted to tolerate levels as high as 0.36%. Strain Z-R was naturally resistant to 0.4% CBC. Since ammonium acetate, carried over by the CBC used in drug formulations and disinfectant solutions, has the potential to support the growth of resistant bacteria and thus make possible the risk of serious infection, it is suggested that regulations allowing the presence of ammonium acetate in CBC solution be reconsidered.